Effect of Crop Rotation with Cavendish Banana Plants on Aluminum Saturation and Effective CEC in Pineapple Plantation, Central Lampung - Ramadhani, Winih Sekaringtyas; Soemarno, Soemarno; Cahyono, Priyo; Rahmat, Ali; Septiana, Liska Mutiara; Prasetyo, Dedy (Journal of Tropical Upland Resources (J. Trop. Upland Res.), 2022)
Low production due to intensive use of chemical fertilizers. In addition, monoculture planting of pineapples can reduce the availability of soil nutrients. The use of chemical fertilizers can create toxic micro nutrients so that they can poison plants. The high level of aluminum can affect the availability of phosphorus in the soil. Efforts to restore soil fertility and reduce aluminum saturation in the soil are crop rotation with cavendis banana plants. The purpose of this study was to determine the effect of planting Cavendis banana on the availability of Aluminum and effective CEC in the soil. This research was conducted from November 2015 to March 2016. The location of this research was conducted at PT. Great Giant Pineapple, Terbanggi Besar, Central Lampung. The locations of this research include PC pineapple (first crop), RC pineapple (ratoon crop), and unloaded bananas. Based on the results of the study, it was shown that the unloading banana location had lower soil aluminum saturation if the compared first crop of pineapple plant and ratoon crop of pineapple plant. In addition, unloaded bananas have a higher effective CEC than pineapple locations. This indicated that crop rotation with Cavendis banana was able to increase cations in the soil, reduce aluminum saturation, so as to increase soil fertility. The low aluminum saturation and high effective CEC were because the unloaded banana location had a higher soil pH and organic matter if the compared the first crop of pineapple plant and ratoon crop of pineapple plant.